Risky business: How standardization as coordination tool in ecosystems impacts firm‐level uncertainty - Toh, Puay Khoon; Pyun, Eugene (Strategic Management Journal, 2024)
Abstract Research Summary Coordination challenges generate uncertainties in ecosystems. Past research suggests that standardization mitigates these challenges, reducing ecosystem‐level uncertainty. But how does it affect firm‐level uncertainty over value‐appropriation? We examine heterogeneity in the latter effect. Using 1996–2010 data on standard‐setting in Information and Communications Technology (ICT) ecosystems and a firm‐level uncertainty measure based on stock option implied volatility, we demonstrate that while standardization reduces uncertainty for firms that own part of the standardized components, it heightens uncertainty for firms that do not, especially when they face strong rivals in complementary technologies or have fewer complementary technologies or production assets themselves. Findings stress that coordination tools enhancing ecosystem‐level value‐creation can end up hurting firm‐level value‐appropriation and worsen uncertainty for some firms in the ecosystem that the tools are meant to help. Managerial Summary In an ecosystem, a firm faces two types of uncertainty—ecosystem‐level uncertainty over how to coordinate with others on developing interoperable parts, and firm‐level uncertainty over whether it can occupy a viable position to capture value. Standardization, a commonly touted solution, reduces the former but not necessarily the latter. Using 1996–2010 data on standard setting in ICT ecosystems and stock option implied volatility, we show that for non‐standard‐owner firms, standardization in fact worsens the latter, especially when they face strong rivals or lack complementary technologies or production assets in areas complementary to the standard. Thus, tools like standardization meant to solve ecosystem‐level coordination problems can end up raising more doubts on firms' ability to capture value and discouraging firms from participating instead of promoting ecosystem growth.